2021
DOI: 10.1155/2021/8835595
|View full text |Cite
|
Sign up to set email alerts
|

A Uniformly Convergent Collocation Method for Singularly Perturbed Delay Parabolic Reaction-Diffusion Problem

Abstract: In this article, a numerical solution is proposed for singularly perturbed delay parabolic reaction-diffusion problem with mixed-type boundary conditions. The problem is discretized by the implicit Euler method on uniform mesh in time and extended cubic B-spline collocation method on a Shishkin mesh in space. The parameter-uniform convergence of the method is given, and it is shown to be ε -uniformly convergent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…They have shown that the proposed scheme is ε-uniform convergent of second-order accurate in the temporal direction and the first-order (up to a logarithmic factor) accurate in the spatial direction. Gelu and Duressa [21] proposed an implicit Euler method for time derivative with uniform mesh and extended cubic B-spline collocation method for space derivative on Shishkin mesh to solve singularly perturbed delay parabolic reaction-diffusion problem subject to mixed boundary conditions. The result obtained is shown to be accurate of O ∆t + N −2 ln 2 N by preserving an -uniform convergence.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown that the proposed scheme is ε-uniform convergent of second-order accurate in the temporal direction and the first-order (up to a logarithmic factor) accurate in the spatial direction. Gelu and Duressa [21] proposed an implicit Euler method for time derivative with uniform mesh and extended cubic B-spline collocation method for space derivative on Shishkin mesh to solve singularly perturbed delay parabolic reaction-diffusion problem subject to mixed boundary conditions. The result obtained is shown to be accurate of O ∆t + N −2 ln 2 N by preserving an -uniform convergence.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Regarding the study of uniform convergence solution, a large amount of literature exists for singularly perturbed non-delay differential equations and many assumptions have been made on the stability [9,12,16]. There have been extensive development studies of singular perturbation problems in the classes of singularly perturbed systems [10,17,18,19,30], singular perturbation problems with two small parameters [4,6,11,27], singular perturbation problems with non-local boundary condition [20], singular perturbation problems with Robin type boundary condition [14,21], singularly perturbed system with Robin type boundary condition [15]. However, in recent years there has been a growing interest in the numerical study of singularly perturbed partial differential equations with delay both in space and time.…”
mentioning
confidence: 99%
“…In some instances, the employment of numerical methods is an appropriate alternative. Some of the well-known numerical and analytical techniques used for nonlinear PDEs include the spectral method [13], the finite element method [14], the collocation method [15][16][17][18], Adomian's decomposition method (ADM) [19,20], the variational iteration method (VIM) [21][22][23], and the homotopy perturbation method (HPM) [24,25]. ADM has been applied to solve non-linear equations in [19,20] by separating the equation into linear and non-linear components.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [13] developed an overlapping Schwarz domain decomposition method for parabolic reaction diffusion problems with time delay. An extended cubic B-spline collocation method on Shishkin mesh has been developed for singularly perturbed delay parabolic reaction diffusion problem with mixed-type boundary conditions in [14]. A numerical method is developed for solving a singularly perturbed parabolic delay differential equation whose solution exhibits a boundary layer behaviour in [15] and singularly perturbed parabolic differential difference equations arising in computational neuroscience in [16].…”
Section: Introductionmentioning
confidence: 99%